Pharmacological treatment of dementia - Schwarz, Stefan; Frölich, Lutz; Burns, Alistair S. (Current opinion in psychiatry, 2012)
Purpose of review: In this article, we discuss new data on currently licensed drugs for dementia and novel developments in the management of neuropsychiatric symptoms in patients with dementia. Recent findings: During the last years, a large body of evidence has been accumulated to support the use of antidementia medication in patients with severe Alzheimer's disease. Combination therapy with acetylcholinesterase inhibitors and memantine for Alzheimer's disease remains controversial, as controlled trials have yielded conflicting results. Memantine is not indicated in patients with mild Alzheimer's disease. Studies on memantine for Parkinson's disease dementia and dementia with Lewy bodies were inconclusive. In adult patients with dementia in the context of Down syndrome, memantine is not effective, and further studies on acetylcholinesterase inhibitors are warranted. There is still no treatment established for patients with vascular or frontotemporal dementia. The efficacy of antidepressants to treat depression associated with dementia is not proven. Treatment of agitation and psychosis in patients with dementia remains a challenge. Summary: Recent systematic clinical reviews and new research on currently available treatment options provide valuable assistance for clinicians to deal with frequent clinical problems in the context of dementia.